The effectiveness of epigallocathechin-3-gallate for treatment of human papillomavirus-driven epithelial neoplasms: a preclinical study. (23rd February 2017) - Yap, Jason; Luesley, David; Woodman, Ciaran; Dawson, Christopher
Abstract: Background: Epigallocathechin-3-gallate (EGCG), the major bioactive polyphenol in green tea, has anticarcinogenic properties in vitro and in vivo. Several recent reports have shown that EGCG affects the expression of human papillomavirus (HPV)-encoded E6 and E7, two oncoproteins required for HPV-driven oncogenesis. Here, we aimed to explore the effects of EGCG on keratinocyte proliferation and differentiation, in addition to HPV18 replication, in a three-dimensional organotypic raft culture system. Methods: Organotypic raft cultures of HPV18-infected keratinocytes cultured at the air–liquid interface for 10 days were treated with EGCG for an additional 10 days before fixation and processing. Raft sections were stained with antibodies specific for various cell proliferation and keratinocyte differentiation markers in addition to tumour suppressor genes. Western blotting was performed on EGCG-treated cells to measure the level of HPV18 E6 and E7 protein expression. Findings: EGCG treatment blocked the ability of HPV18-positive keratinocytes to generate hyperplastic epithelium in raft culture. EGCG reduced cell proliferation as assessed by bromodeoxyuridine label incorporation and Ki67 staining; it upregulated expression of several tumour suppressor genes ( p53 [TP53], p21, pRb ), and impaired productive viral replication (as assessed by HPV18 E4 protein expression), but did not have an effect on keratinocyte differentiation. In culture, EGCG treatment promoted degradation of the E6 and E7 proteins and restored tumour suppressor gene expression. Interpretation: The results of our preclinical study suggest that EGCG inhibits the proliferation of HPV18-infected keratinocytes by enhancing the turnover and degradation of the E6 and E7 proteins, resulting in re-expression of several key tumour suppressor genes. These findings suggest that EGCG could potentially reverse the dysplastic changes induced by oncogenic HPV strains and could be used clinically to treat HPV-induced neoplasia. Funding: Cancer Research UK.